An extension of the Blinder-Oaxaca decomposition to a Continuum of Comparison Groups - Hugo \~Nopo (Inter-American Development Bank, Research Department, 2007)
This paper proposes an extension of the Blinder-Oaxaca decomposition from two to a continuum of comparison groups. The proposed decomposition is then estimated for the case of racial wage differences in urban Peru, exploiting a novel data set that allows the capturing of mestizaje (racial mixtures).
Keywords: C1; J1; J7; O17; 330; Blinder-Oaxaca decomposition; Race; Gender; Informality